On conjugate of saddle-convex functions - Tinianskij, N. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: H. Т. Тынянский. О сопряженности вогнуто-выпуклых функций N. Tinianskis. Apie iškilai-įgaubtų funkcijų sujungtinumą